2013
DOI: 10.5005/jp-journals-10024-1313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effect of Different Cavity Disinfectants on Shear Bond Strength of Composite Resin to Dentin using Two-Step Self-Etch and One-Step Self-Etch Bonding Systems: A Comparative in vitro Study

Abstract: Aim and objectives: To evaluate the effect of 2% chlorhexidine, 2% sodium hypochlorite, 3% hydrogen peroxide on shear bond strength of composite resin to dentin using two-step and onestep self-etch bonding systems and to study the mode of failure of specimens under stereomicroscope. Materials and methods: Eighty extracted sound human posterior teeth were used. The occlusal surfaces were ground to expose the dentin and were then randomly divided into 4 main groups. In group I, no cavity disinfectant was used an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Group II (2.5% sodium hypochlorite) showed statistically significant differences in microleakage scores when compared with the negative control group. This finding is in accordance with other studies conducted by Frankenberger et al, 18 Bansal and Tewari, 31 Ercan et al, 11 Mirzaei et al, 32 Pattanaik and Chandak, 33 and Reddy et al 15 Study by Lai et al suggested greater microleakage and poor adaptation of resin to dentin surface with different adhesive system after sodium hypochlorite treatment could be associated with the oxidizing effect of sodium hypochlorite and its reaction by-products, thus causing interruption in the interfacial polymerization of adhesives. The premature chain termination and incomplete polymerization of adhesives could be related to residual reactive free radicals in dentin with sodium hypochlorite treatment reacting with propagating free vinyl radicals generated during light activation of the adhesive resin, leading to increased microleakage.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Group II (2.5% sodium hypochlorite) showed statistically significant differences in microleakage scores when compared with the negative control group. This finding is in accordance with other studies conducted by Frankenberger et al, 18 Bansal and Tewari, 31 Ercan et al, 11 Mirzaei et al, 32 Pattanaik and Chandak, 33 and Reddy et al 15 Study by Lai et al suggested greater microleakage and poor adaptation of resin to dentin surface with different adhesive system after sodium hypochlorite treatment could be associated with the oxidizing effect of sodium hypochlorite and its reaction by-products, thus causing interruption in the interfacial polymerization of adhesives. The premature chain termination and incomplete polymerization of adhesives could be related to residual reactive free radicals in dentin with sodium hypochlorite treatment reacting with propagating free vinyl radicals generated during light activation of the adhesive resin, leading to increased microleakage.…”
Section: Resultssupporting
confidence: 93%
“…4 Growth of microorganisms under a restoration results in tooth hypersensitivity, weakening of bond strength, development of secondary caries, pulpal inflammation, and necrosis of the pulp. 15 It is believed that gross disinfection of the cavity preparation before inserting the restorative material is the best that can be achieved to reduce the potential risk of sensitivity and residual caries. 16 In the last decades, many chemicals have been tested as cavity disinfectants, including chlorhexidine gluconate, benzalkonium chloride, iodine potassium iodide/copper sulfate, fluoride, sodium hypochlorite, etc.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] and Reddy et al . [ 23 ] where resin-bond strength declined when composite resins with different bonding systems were used. This is because the collagen matrix and dentinal tubules may have retained some amount of H 2 O 2 that eventually decomposed into oxygen and water.…”
Section: Discussionmentioning
confidence: 99%